Exact Solutions to the Nonlinear Schrödinger Equation with Time-Dependent Coefficients - Mai, Xin-Lei; Li, Wei; Dong, Shi-Hai (Advances in High Energy Physics, 2021)
In this paper, a trial function method is employed to find exact solutions to the nonlinear Schrödinger equations with high-order time-dependent coefficients. This system might be used to describe the propagation of ultrashort optical pulses in nonlinear optical fibers, with self-steepening and self-frequency shift effects. The new general solutions are found for the general case a0≠0 including the Jacobi elliptic function solutions, solitary wave solutions, and rational function solutions which are presented in comparison with the previous ones obtained by Triki and Wazwaz, who only studied the special case a0=0.